Economic indicators (UN ECLAC SantiagoCL, 1997)
Presents indicators on the economic, social and business situation for most of the countries that made a commitment in December 1994 to participate in the establishment of a Free Trade Area of the Americas. However due to insufficient information on some countries, notably those of the Caribbean, the publication does not cover all 34 countries that signed the Declaration of Principles and Plan of Action of the Summit of the Americas.
Located in the Statistics Section